2007
DOI: 10.1248/bpb.30.1336
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Affects Development of Zebrafish Embryo

Abstract: Curcumin (diferuloylmethane) is a dietary polyphenol derived from the rhizomes of turmeric (Curcuma longa). For a long time, curcumin has been applied as an anti-inflammatory, 1) anti-oxidative, 2-4) and anti-carcinogenic 5) compound. The multiple therapeutic effects of curcumin result from its ability to modulate enzyme activities and gene expression. For example, curcumin has been shown to down-regulate the activities of several transcription factors, including NF-kappa B, AP-1, and Egr-1, as well as growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…Archetypal anti-aging/anti-cancer polyphenols, such as curcumin and resveratrol, have been shown to operate as “double-edged swords”, such that in vitro experiments reveal carcinogenic and pro-oxidant effects, in addition to anticancer and antioxidant effects. Accordingly, these polyphenols have been shown to exert embryotoxic and teratogenic effects using zebrafish embryos as disease models [44-50]. The PASS predictions obtained in the present study similarly predict carcinogenic, embryotoxic, and teratogenic effects for the dialdehydic forms of OA and DOA.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Archetypal anti-aging/anti-cancer polyphenols, such as curcumin and resveratrol, have been shown to operate as “double-edged swords”, such that in vitro experiments reveal carcinogenic and pro-oxidant effects, in addition to anticancer and antioxidant effects. Accordingly, these polyphenols have been shown to exert embryotoxic and teratogenic effects using zebrafish embryos as disease models [44-50]. The PASS predictions obtained in the present study similarly predict carcinogenic, embryotoxic, and teratogenic effects for the dialdehydic forms of OA and DOA.…”
Section: Discussionsupporting
confidence: 67%
“…As green-colored atoms reflect a positive impact on a given activity while the red-colored atoms reflect a negative impact on the same activity, it should be noted that the chemopreventive mechanisms of action that are significantly predicted for the open dialdehydic forms of OA and DOA, but not for their cyclic hemiacetalic isomers mostly involve all of the atoms involved in the polyphenolic structure of DOA. Remarkably, as observed for many drugs with potential antineoplastic and chemopreventive properties, including curcumin and resveratrol [44-50], the open dialdehydic forms of OA and DOA are predicted to exhibit teratogenic and embryotoxic properties.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies on other types of cells (Kang et al, 2005;Marcu et al, 2006;Wu et al, 2007), we first used several different doses of curcumin and different treatment durations. The results showed that curcumin could repress HAT activities in cardiac myocytes effectively with 30 μM curcumin for 24 h. The treatment in cultured cardiac myocytes caused a maximal inhibitory effect without significant cell morphological changes or other cell damages.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [24] reported that the teratogenic effects of curcumin treatment on zebrafish embryos included bent or hook-like tails, spinal column curving, edema in pericardial sac, retarded yolk sac resorption, and shorter body length. The teratogenic effects we found in zebrafish embryos exposed to our ethanol extract were similar.…”
Section: Teratogenic Effects Of Ethanol Extract On Zebrafish Embryosmentioning
confidence: 99%